2000
DOI: 10.1046/j.1365-2133.2000.03773.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of red and green light in the treatment of Bowen’s disease by photodynamic therapy

Abstract: Green light is less effective than red light, at a theoretically equivalent dose, in the treatment of Bowen's disease by topical ALA-PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 19 publications
2
92
0
2
Order By: Relevance
“…1 On the other hand, another clinical ALA-PDT study found that green light (540 AE 15 nm) is less effective than red light (630 AE 15 nm) in the treatment of Bowen's disease. 5 These results are inconsistent for different diseases, which may imply that treatment wavelength is not the only cause of different therapeutic outcomes of ALA-PDT.…”
Section: Introductionmentioning
confidence: 85%
“…1 On the other hand, another clinical ALA-PDT study found that green light (540 AE 15 nm) is less effective than red light (630 AE 15 nm) in the treatment of Bowen's disease. 5 These results are inconsistent for different diseases, which may imply that treatment wavelength is not the only cause of different therapeutic outcomes of ALA-PDT.…”
Section: Introductionmentioning
confidence: 85%
“…[69][70][71][72][73] Results for ALA, [69][70][71][72] and MAL 73 are presented separately; AEs were not reported for the only trial using verteporfin.…”
Section: Results Of Safetymentioning
confidence: 99%
“…In the trial by de Haas et al, 69 pain during treatment was experienced by five patients in the twofold-illumination group and by none of the patients in the single-illumination group. In the trial by Morton et al 70 comparing red and green light, no significant difference in pain was observed between the treatment groups.…”
Section: Ala-pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…The few recurrences that are seen seem to result from the failure of the ALA to penetrate the tumor; weak solutions of dimethylsulfoxide or desferrioxamine applied before ALA increases drug penetration and improves cure rates [60,61]. ALA PDT can also be used to successfully treat Bowen's disease, giving significantly higher CR rates (75%-88%) than 5-fluorouracil (50%) or cryotherapy (48%), provided that illumination is with penetrating red light [62][63][64]. One drawback of ALA PDT is that the first few minutes of illumination can be very painful.…”
Section: Skin Cancermentioning
confidence: 99%